Effect of isothermal aging to the intermetallic compound (IMC) growth of Sn-0.7Cu-1.0Si₃N₄ composite solder on copper substrate - Najib Saedi, Ibrahim
The excessive growth of intermetallic compound (IMC) layer on solder joints has become a challenging to the electronic packaging industry. Excessive IMC growth is a barrier for the reliability of solder joints and the suppression of IMC is a target for most solder manufacturers. Thus, research study of IMC formations and growth are always open for discussion and development. A new Sn-0.7Cu-Si3N4 composite solder has been fabricated in order to overcome the above mentioned problem. In this study, isothermal aging test on the new SnCu-Si3N4 composite solder were carried out at 50°C, 75°C, 100°C,125°C and 150°C for 24, 240, 480, 600 and 720 hours. The same methodology was carried out to monolithic Sn-0.7Cu solder for comparison. SEM-EDS and XRD were used for elemental and compound analysis respectively. It is seen that Cu3Sn and Cu6Sn5 IMCs have remained as the IMC phases in both solders. From observation, Si₃N₄ addition has not created any other phases after soldering process. After isothermal aging, the intermetallic thickness has increased with increasing of temperature and time while the morphology has changed from scallop to planar type. However, the IMC growth rate for composite solder is low compared to Sn-0.7Cu solder. The diffusion kinetics for Sn-0.7Cu-Sn3N4 is lower than monolithic Sn-0.7Cu solder which had resulted with larger activation energy value. The activation energy value for the solder composite is 15.5kJ/mol while for Sn-0.7Cu solder is 14.7kJ/mol. For mechanical testing, shear test was carried out by using Instron machine. The overall shear strength of Sn-0.7Cu-Si₃N₄ is higher than Sn-0.7Cu solder. Therefore, the presence of silicon nitride as reinforcement is believed has suppressed IMC formation and has improved the strength of Sn-0.7Cu-Si₃N₄ composite solder.